FACTORS AFFECTING THE FINANCIAL PERFORMANCE OF ANH QUAT HOSPITAL, TAN YEN DISTRICT, BAC GIANG PROVINCE IN THE PERIOD 2021-2023 (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze key factors affecting the financial performance of Anh Quất General Hospital, Tan Yen Commune, Bac Giang Province, during 2021–2023.Methods: A qualitative research design was used. Ten in-depth interviews were conducted with representatives from the hospital’s board of directors, functional department leaders, collaborating physicians, and the Provincial Department of Health, along with two focus group discussions with hospital staff (administrative and clinical departments) in August 2024. The qualitative topics focused on internal and external factors affecting the hospital’s financial outcomes.Results: Positive influencing factors included universal health insurance coverage policies, government support for healthcare socialization, effective application of information technology, a strategy for sustainable development and expansion, investment in modern medical equipment, and a young, enthusiastic workforce. Negative factors included the hospital’s new private-sector structure, the COVID-19 pandemic, competition from other health facilities in the area, insufficient coordination with the social insurance agency, limited depth of professional expertise, and lack of experience.Conclusion: In addition to strategies to improve service quality and human resources, the hospital needs to strengthen the use of information technology in financial management and clinical services; collaborate closely with the Social Insurance Agency to provide training and enhance activities of the health insurance cost-control team for reimbursement procedures; reinforce hospital marketing; and establish clear and specific expenditure regulations.
Keywords: hospital financial performance, hospital financing management, internal influencing factors, external influencing factors.